New Indo-Aryan associative plural markers derived from Old Indo-Aryan apara ‘other’ and their further grammaticalization - Renkovskaya, Evgeniya (Lingua Posnaniensis, 2020)
The paper deals with associative plurals in New Indo-Aryan languages, which are derived from the Old Indo- Aryan apara ‘other’. These markers are found in a large number of NIA languages, but in many of these languages they underwent further grammaticalization into other grammatical units, such as honorific particle, standard plural marker, definiteness marker, marker of inalienable possession etc. Among the factors which underlie this grammatical development, contacts with non-Indo-Aryan languages play a significant role.